Evaluation of post-harvest quality of some mango (Mangifera indica) genotypes during storage - AUNG, AYE MOH MOH; SHARMA, R R; SETHI, SHRUTI; SRIVASTAV, MANISH (The Indian Journal of Agricultural Sciences, 2020)
Mango (Mangifera indica L.) is known as the ‘King of the fruits’ in India and contributes largely to total fruit production. In addition to several superior varieties of mango, several new hybrids or varieties are added every year which have not been assessed for their storage behaviour. Hence, we conducted study on storage behaviour of 12 hybrids/varieties grown under Delhi conditions. For this, fruits of selected varieties were harvested at full maturity and after ripening, stored at 12°± 1ºC and 85–90% RH for further observations at 3 days interval. Our results revealed that the PLW was the lowest in Pusa Arunima (4.8%) which increased with the increase in storage period. Interestingly, genotypes such as Amrapali, Pusa Arunima, Pusa Lalima, Pusa Pratibha, Pusa Shreshth, Pusa Surya and Sensation exhibited <10% PLW. Similarly, total carotenoid content was the highest in Pusa Arunima (7.47 mg/100g).The overall acceptability score was the highest in Pusa Arunima (8.54) and the lowest in Langra (6.20). Based on these observations, it can be revealed that Pusa Arunima excelled all other varieties/hybrid in storage life (12 days) and other quality attributes.